“Should Women Smile at Mona Lisa Smile (2003)?” A Feminist Critical Discourse Analysis of Gender Representation - Solong, Alicia Ferani; Petrus Jacob Pattiasina (Universitas Negeri Surabaya, 2025)
This article applies Feminist Critical Discourse Analysis (FCDA) to Mona Lisa Smile (2003) to examine how nostalgic Hollywood cinema both reinscribes and subverts 1950s gender norms. Five strategically selected scenes (comprising 23 dialogue turns and accompanying visuals) were analysed using Lazar’s (2007) three-stage FCDA, supported by Eckert and McConnell-Ginet’s (2013) linguistic frameworks. The analysis reveals a sustained ambivalence, where feminist language is frequently undermined by visual and narrative conventions that re-centre domestic ideals. Drawing on Butler’s theory of performativity, Bourdieu’s concept of symbolic power, and audience reception studies (Radner 2021; Negra 2009), the study situates the film within broader patterns of postfeminist media. Comparative references to other